2009
DOI: 10.1175/2008jcli2626.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Response of the Arctic Freshwater Budget to Extreme NAO Wind Forcing

Abstract: The authors investigate the response of the Arctic Ocean freshwater budget to changes in the North Atlantic Oscillation (NAO) using a regional-ocean configuration of the Massachusetts Institute of Technology GCM (MITgcm) and carry out several different 10-yr and 30-yr integrations. At 1 / 6 8 (;18 km) resolution the model resolves the major Arctic transport pathways, including Bering Strait and the Canadian Archipelago. Two main calculations are performed by repeating the wind fields of two contrasting NAO yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 69 publications
5
57
0
Order By: Relevance
“…We provide here a brief description of the physical-biogeochemical coupled model used to generate the "RIV run". The MITgcm (MIT general circulation model) ocean-sea ice model (Nguyen et al, 2009(Nguyen et al, , 2011Losch et al, 2010;Condron et al, 2009) has a variable hor- (Menemenlis et al, 2005). Atmospheric forcings (10 m winds, 2 m air temperature and humidity, and downward long-and shortwave radiation) are taken from the 6-hourly data sets of the Japanese 25-year ReAnalysis (JRA-25; Onogi et al, 2007).…”
Section: -D Physical-biogeochemical Model Datamentioning
confidence: 99%
“…We provide here a brief description of the physical-biogeochemical coupled model used to generate the "RIV run". The MITgcm (MIT general circulation model) ocean-sea ice model (Nguyen et al, 2009(Nguyen et al, , 2011Losch et al, 2010;Condron et al, 2009) has a variable hor- (Menemenlis et al, 2005). Atmospheric forcings (10 m winds, 2 m air temperature and humidity, and downward long-and shortwave radiation) are taken from the 6-hourly data sets of the Japanese 25-year ReAnalysis (JRA-25; Onogi et al, 2007).…”
Section: -D Physical-biogeochemical Model Datamentioning
confidence: 99%
“…Fluxes of momentum into ice due to the overlying atmospheric winds and momentum fluxes between sea ice and the ocean are calculated by solving for the momentum balance at each surface grid column (Hibler and Bryan, 1987). This model configuration was previously used to study the Arctic freshwater budget (Condron et al, 2009). Modelling studies of Condron et al (2009) compared to observations by Serreze et al (2006) concluded that this model configuration is able to realistically represent the freshwater budget of the AO, including the import and export of freshwater from the Bering and Fram straits and from the Canadian Archipelago.…”
Section: The Physical Modelmentioning
confidence: 99%
“…But importantly, it is recognized that extra exports of sea ice, episodic or otherwise, or a more continuous nature of the freshening and flushing of water from the Arctic basin to the northern North Atlantic basins (e.g., Condron et al 2009) would serve as key negative feedbacks for the MOC/THC oscillation. Dickson et al (2007) highlighted the potentially greater importance of combined ice and freshwater outflows from the Arctic Ocean basin through the Canadian Arctic Archipelago/Nares Strait/Baffin Bay/Davis Strait pathways under a warm Arctic and low-ice-volume climatic regime.…”
Section: Empirical Evidence and Mechanistic Explanation For Interrelamentioning
confidence: 99%
“…7 Detailed computer modeling (Proshutinsky et al, 2002;Moon and Johnson, 2005;Dukhovskoy et al, 2006;Condron et al, 2009) shows how the oscillations between the anticyclonic and cyclonic circulation regimes, involving contraction and expansion of the Beaufort Gyre, are affecting how Arctic sea ice and freshwater are stored and released to the northern North Atlantic Ocean. (2007) suggest that the vigor of ISOW is controlled by the transport and characteristics of the Labrador Sea water farther to the west (Jungclaus et al, 2005).…”
Section: Empirical Evidence and Mechanistic Explanation For Interrelamentioning
confidence: 99%
See 1 more Smart Citation